Nutrition-inflammation marker enhances prognostic value to ECOG performance status in overweight or obese patients with cancer - Zhang, Xi; Zhang, Qi; Tang, Meng; Zhang, Kang-Ping; Zhang, Xiao-Wei; Song, Meng-Meng; Ruan, Guo-Tian; Sun, Qiang; Li, Wei; Xu, Hong-Xia; Cong, Ming-Hua; Deng, Li; et al. (JPEN. Journal of parenteral and enteral nutrition, 2023)
Overweight or obese cancer patients are more likely to develop a proinflammatory status. The aim of this study was to investigate whether the nutrition-inflammation marker can provide additional prognostic information on top of well-established Eastern Cooperative Oncology Group performance status (ECOG-PS) in overweight or obese patients with cancer. A total of 1667 overweight or obese cancer patients were enrolled in this study. We assessed the prediction accuracy of 10 nutrition-inflammation markers by time-dependent receiver operating characteristic (ROC) and elucidated their association with overall survival by the Kaplan-Meier method and a Cox model. In this analysis, the majority of patients had a good performance status (ECOG-PS score ≤1; 88.3%). Both the area under ROC curves and the C-index of the lymphocyte-C-reactive protein ratio (LCR) demonstrated that LCR was the most significant nutrition-inflammation marker correlated with survival. In patients with good ECOG-PS, a low LCR was significantly associated with poorer prognosisand enhanced the predictive ability of one-year mortality. For specific tumor types, a low LCR was an independent prognostic factor for lung cancer, upper gastrointestinal cancer, and colorectal cancer, and it tended to be a significant predictor for breast cancer. In addition, those patients with a combined low LCR and poorer ECOG-PS (ECOG-PS score >1) showed the worst prognosis. The LCR is more strongly associated with overall survival than other nutrition-inflammation markers, and it is able to further detect patients with worse prognosis on top of ECOG-PS in overweight or obese patients with cancer.